CORAK BUDAYA BIROKRASI PADA MASA KERAJAAN, KOLONIAL BELANDA HINGGA DI ERA DESENTRALISASI DALAM PELAYANAN PUBLIK - Nur Hasan (Jurnal Hukum, 2012)
The composition of the traditional government bureaucracy is still followed by the imperial bureaucracy, by dividing the affairs of government affairs in the kingdom and royal affairs. quality of the bureaucracy and officials expected nothing but the creation of a government apparatus that is reliable, able to carry out the overall general government administration, development and public services efficiently, effectively and professionally. Performance can be defined as the level of achievement in other words, the performance is the level of achievement of the organizational goals of the region. So to determine the performance of Local Government can be seen from how it looks in achieving results and how the results can be achieved in accordance with predetermined targets.Keywords: Shades Of Culture, Bureaucracy, Public Service